Nucleocytoplasmic transport: more than the usual suspects - Swaminathan, Sowmya; Melchior, Frauke (Developmental cell, 2002)
A paper in the August 9 issue of Cell describes a novel role for the nucleoporin Npap60/Nup50 as a soluble cofactor in importin-α:β-mediated nuclear protein import. These findings add a new dimension of complexity to the current understanding of protein transport pathways.
Gesehen am 04.09.2023